Management of Lutha Visha (Spider Poison) -A Case Report. - Salwa; Arun, B (International Research Journal of Ayurveda & Yoga, 2023)
As per modern view, more than 20000 species of Spiders are identified and classified into 60 families. Most of them are not dangerous. In Ayurveda Visha mainly classified as Sthavaram and Jangamam. Sthavaram includes plant origin whereas Jangamam includes animal origin like snake, spider, scorpion and insects etc. The detailed explanation of Luthavisha origin, symptoms, mode of poisoning and treatment is available in our classical texts. Acharya Susrutha describes 16 species of Lutha and Vagbhata describes about 28 varieties. Luthavisha (spider poisoning) is very common in Kerala especially in lower socio-economic groups. Here is a case of 6 months old girl child who presented with reddish blue, soft, raised, spreading lesions with pustules, which produce severe irritation to the child and was diagnosed as Luthavisha. Generally, the poison of all spiders has properties of all 3 dosas with predominance of Pita and Kapha. So, the line of treatment includes Pitakaphahara treatment along with Srothoshodana and Rakthaprasadana. A remarkable change has been observed as the lesion stops spreading and pustules get dried up.